Solving nonperturbative flow equations - Adams, Jennifer A.; Berges, Jürgen; Freire, Filipe; Wetterich, Christof (Modern physics letters, 1995)
Nonperturbative exact flow equations describe the scale dependence of the effective average action. We present a numerical solution for an approximate form of the flow equation for the potential in a three-dimensional N-component scalar field theory. The critical behavior, with associated critical exponents, can be inferred with good accuracy.
Gesehen am 22.11.2017